Strategi Pemasaran PT. Prudential Life Assurance Di Kota Binjai - Muhmmad Riduan; Fauzi Arif Lubis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Insurance as one of the financial institutions engaged in the field of coverage is a modern institution resulting from the findings of the western world which was born along with the spirit of enlightenment. The purpose of this research is to find out how the marketing strategy of PT Prudential Life Assurance Binjai. The method used in this research is descriptive qualitative method. Insurance in Islamic literature has more social nuances than economic or profit oriented (business profits). This is due to the aspects and help that are the main basis for upholding insurance practices in Islam. The results of this study are the marketing strategy carried out by PT Prudential Life Assurance Bijai is that the company recruits, trains and motivates its employees related to the 5P component, namely Product, Price, Place, Promotion, and People.